Synthesis, structure, and reactivity of diazoketiminato complexes of platinum(II) and palladium(II): cytotoxic properties of a platinum complex - Pratihar, Jahar Lal; Shee, Biswaranjan; Pattanayak, Poulami; Patra, Debprasad; Bhattacharyya, Arindam; Puranik, Vedavati G.; Hung, C. H.; Chattopadhyay, Surajit (European Journal of Inorganic Chemistry, 2007)
{Reaction of the 2-(arylazo)anilines Ar-N = N-C6H4NH2 [
Keywords: CFD; hydro processing; scale-down; scale-up; trickle bed